Reducing the Salinity of the Produced Water from Oil Field Using Activated Carbon Extracted from Waste Date Kernel - Samba, Mohammed; Li, Yiqiang; liu, Zheyu; Farhat, Masouda; Ebrahim, Taha; Milad, Mohammed; Fenniche, Fares; Elsharaf, Mahmoud (Journal of Pure & Applied Sciences, 2023)
Oil production operations are commonly divided into three periods: "Primary, Secondary and Enhanced Oil Recovery EOR”. Primary recovery is considered as the initial production stage, resulting from the displacement of natural derive mechanisms that exist in a reservoir. Secondly, the secondary recovery period which is the water flooding, or gas injection. The final stage period is EOR period, which involves the injection of external material into a reservoir. Where the injected slug interacts with the reservoir rock or oil system to create favorable conditions in order to enhance the oil recovery. The produced water can be used as the water flooding during the secondary recovery, but the high salinity of the formations yields a low recovery factor. Thus, some materials have been used to reduce the water salinity during the production in order to reinject it into the reservoir and cause a high recovery factor. The challenge to obtain an economic material which is able to reduce the salinity in the oil fields is still at stake. Thus, many materials need to be applied in order to test its ability to reduce the water salinity. The activated carbon extracted from waste date kernel have not used yet in this area. In the present paper, the activated carbon was prepared at lab by following specific procedures. Where, a different size of activated carbon extracted from date kernel used to treat the saline water, which later will be used for a spontaneous imbibition test for sandstone core samples after saturated with crude oil. A spontaneous imbibition test consisting of three scenarios of activated carbon at various temperatures and later compared with untreated reservoir water. In this study, the spontaneous imbibition test was performed at room temperature and oven temperature including (45, 55, and 70 ℃). The results showed that activated carbon is a useful material to reduce the water salinity. Where, the best oil recovery was at a treated water with activated carbon volume (0.125), which was (70.41%), that was at the maximum used temperature.